Clinical application of electroacupuncture in enhanced recovery after surgery - Mao, Yu; Yang, Lifang (Frontiers in Rehabilitation Sciences, 2023)
Enhanced recovery after surgery (ERAS) is currently the recommended surgical strategy, the main content of which is to reduce perioperative stress response and postoperative complications through perioperative multimodal analgesia and intensive surgery. Since ERAS was introduced, many rehabilitation medicine teams have been deeply involved, including physical therapy, occupational therapy, nutrition therapy and psychological counseling. However, ERAS lacks several powerful means to address perioperative prognostic issues. Therefore, how to further improve the effects of ERAS, reduce perioperative complications and protect vital organ functions has become an urgent problem. With the continuous development of traditional Chinese medicine, electroacupuncture (EA) has been widely used in various clinical applications, and its efficacy and safety have been fully proved. Recent studies have shown that the application of EA in ERAS has had an important impact on rehabilitation researches. In terms of reducing complications, the therapeutic effects of EA treatment mainly include: reducing pain and the use of analgesics; Improvement of postoperative nausea and vomiting; Postoperative immune function treatment; Relieve anxiety and depression. In addition, EA also protects the recovery of physiological functions, including cardiovascular function, cerebrovascular function and gastrointestinal function, etc. To sum up, the complementary strengths of EA and ERAS will allow them to develop and combine. This review discusses the potential value and feasibility of EA in ERAS from the aspects of improving perioperative efficacy and protecting organ functions.